What Symbolic Meaning Would Peirce Find in the Raspati Dance at the Galura Kencana Studio in Garut? - Muhamad Rifki Ilhami; Ria Sabaria; Fitri Kurniati (Gondang: Jurnal Seni dan Budaya, 2026)
This study examines the symbolic meanings embedded in the Raspati Dance performed at Sanggar Galura Kencana, Garut Regency, using the semiotic perspective of Charles Sanders Peirce. It aims to identify and interpret the system of signs found in the choreographic structure, movement vocabulary, makeup, and costume as representations of Sundanese women’s leadership values in education. The study employs a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and literature review, and triangulation was applied to ensure validity. The analysis is based on Peirce’s triadic model, which consists of the sign, object, and interpretant, to understand how visual and kinetic elements function as cultural signs within the performance. The findings show that the movement sequences of the Raspati Dance do not merely serve aesthetic purposes, but also represent values such as perseverance, intelligence, solidarity, and leadership vision among women. The makeup and costume further reinforce the visual dimension, highlighting the image of Sundanese women as graceful, firm, and dignified. All the interconnected elements of the dance create a symbolic narrative that reflects women's struggle to gain knowledge and contribute to societal development. In this sense, the Raspati Dance can be understood as a form of cultural expression that combines artistic creativity with symbolic meanings rooted in the social and cultural values of Sundanese society.